Pelatihan Pengelolaan Keuangan Berbasis Teknologi bagi Pelaku UMKM di Desa Banjarsari Kecamatan Cerme Kabupaten Gresik. - Tri Ariprabowo; Ch. Menuk Sri Handayani; Bayu Adi; Subakir (Fakultas Ekonomi, Universitas PGRI Adi Buana Surabaya, 2022)
This community service activity is focused on the dissemination and training for financial report preparation based on information technology for small and medium enterprises. The management of small and medium business in Banjarsari Village, Cerme, Gresik had not fully used information technology in the preparation of their financial statements. The method which used in this community service activity was a socialization method about using of information technology in financial management preparation and continued by conducting training and practice in preparing financial reports using information technology. The results of the community service activities showed that small and medium businesses were highly motivated to compile their financial reports using information technology and have been able to record transactions using computer applications. The results of this community service activity are expected to increase transparency and accountability in financial management for small and medium enterprises.